PEMBELAJARAN MENULIS PUISI DENGAN METODE PENGALIRAN IMAJI BERBANTUAN MEDIA POHON PINTAR PADA PESERTA DIDIK KELAS X SMA TUNAS BARU CIPARAY - Rd.Mira Putri Oktaviani; Dindin, Lili Sadeli (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This research was motivated by several problems found by researchers in Grade X Students of Tunas Baru Ciparay High School, including the low ability to write poetry due to conventional learning methods. Therefore, the purpose of this study is to determine the ability of researchers in planning, implementing, and assessing poetry writing learning using the imagery flow method in grade X students of high school. In addition, to determine the ability of grade X students of high school in writing poetry before and after using the imagery flow method. Finally, to determine the effectiveness of the imagery flow method used in learning to write poetry in grade X students of high school. This study applies the classroom action research method. The research process was carried out in three cycles, where each cycle consists of two meetings. In this study, an Unequal Control Group design was used. This design includes the presence of a control group, but is not fully able to control external variables that can affect the results of the experiment. Research Results showed that there was an increased in Grade X Students of SMA Tunas Baru Ciparay in learning to write poetry after using the imagery flow method assisted by smart tree media.